Modeling Skin Inflammation Using Human In Vitro Models. Issue 3 (8th March 2021) - Boarder, Erika; Rumberger, Beth; Howell, Michael D.
Abstract: Skin is made up of an epidermis and, dermis which serve as a barrier against physical and environmental threats. Keratinocytes make up greater than 95% of the epidermis and form different layers based on their level of differentiation. Millions of individuals suffer from skin diseases, which are characterized by significant barrier disruption and inflammation. Investigators previously relied on animal models to investigate inflammatory skin diseases; however, technological advances have enabled the use of physiologically human skin models to investigate the effects of inflammatory mediators on the structure and function of skin cells. In this article, we describe two protocols using keratinocytes to investigate tumor necrosis factor alpha (TNF‐α) and interferon gamma (IFN‐γ) driven skin inflammation as a surrogate for psoriasis, vitiligo, and other autoimmune skin diseases driven by these cytokines. © 2021 Wiley Periodicals LLC. Basic Protocol 1 : Preparing a HaCaT keratinocyte culture Basic Protocol 2 : 3‐Dimensional organotypic skin cultures to assess TNF‐α and IFN‐γ driven skin inflammation